2006
DOI: 10.1200/jco.2005.04.5799
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities: Racial Disparities in Adjuvant Breast Cancer Treatment

Abstract: Minority women with early-stage breast cancer have double the risk of white women for failing to receive necessary adjuvant treatments despite rates of oncologic consultation similar to those for white women. Oncology referrals are necessary to reduce treatment disparities but are not sufficient to ensure patients' receipt of efficacious adjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
266
9
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(284 citation statements)
references
References 28 publications
7
266
9
1
Order By: Relevance
“…34 Several studies have revealed disparities because of race/ethnicity, older age, and geographic location in breast cancer care, including the receipt of RT after BCS. 12,13,27,[35][36][37][38][39][40][41][42][43] The present study, however, is the first to document a disparity in the receipt of RT because of race/ethnicity and SES in a single region within the state of California, and an age disparity throughout the entire state. LA, the most populous of the California regions with the largest number and highest percentage of African American and Hispanic residents in this study, is the only region where the association of RT after BCS varied by race/ethnicity.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…34 Several studies have revealed disparities because of race/ethnicity, older age, and geographic location in breast cancer care, including the receipt of RT after BCS. 12,13,27,[35][36][37][38][39][40][41][42][43] The present study, however, is the first to document a disparity in the receipt of RT because of race/ethnicity and SES in a single region within the state of California, and an age disparity throughout the entire state. LA, the most populous of the California regions with the largest number and highest percentage of African American and Hispanic residents in this study, is the only region where the association of RT after BCS varied by race/ethnicity.…”
Section: Discussionmentioning
confidence: 90%
“…6,7 Racial and geographic disparities in breast cancer outcomes have been well documented, 3,[8][9][10][11][12] and minority women with early stage breast cancer have been reported to have double the risk for failing to receive necessary adjuvant treatments when compared with white women. 13 We have been investigating breast cancer in California with particular emphasis on subtypes, age, and race/ethnicity. [14][15][16][17] In 2009, we presented preliminary results indicating that there were differences in the use of RT after BCS in the 8 regions of California defined by the California Cancer Registry.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Differences in treatment according to race have been noted in adult diseases such as breast cancer, coronary heart disease, hypertension and schizophrenia. [17][18][19][20] We postulated that differences in delivery patterns for breech presentation may also exist by race, thereby contributing to racial disparities in neonatal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A landmark study by Elmore et al (2005) revealed racial differences among AA women along the illness trajectory, including timeliness and identification of their first symptoms, diagnosis, and subsequent treatment. AA women are less likely to receive radiation therapy following breast-conserving surgery (Bickell et al, 2006). Even with equal access health care systems such as Medicare, there appears to be a difference in the treatment of breast cancer among AA women (Smith et al, 2010).…”
Section: Introductionmentioning
confidence: 99%